KAJIAN PENGEMBANGAN JARINGAN DISTRIBUSI AIR BERSIH PADA PDAM TIRTA BARITO KOTA BUNTOK - Diana, Eka Wahyu; Sholichin, Mohammad; Haribowo, Riyanto (Jurusan Teknik Pengairan, Fakultas Teknik, Universitas Brawijaya, 2020)
PDAM of Buntok City is a supplier of clean water needs for the area of Buntok Kota, Hilir Sper, Jelapat and Pamait villages. Utilization of discharge is not optimal and water loss is service constraint. This study aims to realize a distribution network system that is able to serve up to 2038 by evaluating the existing conditions of clean water distribution networks,network development plans, water quality and economic analysis to determine water prices. The results of hydraulic simulation show that the existing conditions of pressure and headloss gradient meet technical criteria while the speed is not up standard. Then the development simulation meets the technical requirements of 0,3-4,5 m/s, headloss gradient 0-15 m/km, pressure 0,5-8 atm. Simulation of residual injection chlorine concentration at the inlet reservoir of 0,4 mg/l are given constantly. The results of residual chlorine simulation meet the criteria of 0,383-0,395 mg/l. Economic analysis found that water prices were Rp.6.100,00/m³,BCR 1,23 IRR 12,14% and 11-year BEP. Analysis of the ability of the community to pay Rp.4.200/m³, the amount of government subsidy is Rp.13.905.747.800,00.